The Standard of Disciplining Zakat Organization’s Investments and Suggest a Proposal for an Investment - Shammout, Mohammad Marwan (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
Zakat organizations should be highly organized and disciplined, because their role is an intermediary at managing Zakat funds and the rights of Zakat’s deservers, as they are not partners with those funds, and have to be honest in their dealings with them, which makes the nature of their work is highly sensitive, so that the trust and good reputation are their main capital that ensures their continuity and success, so if they lost their reputation, the confidence of Zakat’s payers will decrease or eliminate. The same result would appear and may exposure these organizations to accountability, if they invest its surplus of Zakat funds without any controls or never invest these funds and leaves them exposed to the risks of inflation.